2010
DOI: 10.3748/wjg.v16.i4.431
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized prevalence and 5-year mortality for IBD: Record linkage study

Abstract: CD and UC have distinct demographic profiles. The higher prevalence of hospitalized CD in more deprived areas may reflect higher prevalence and higher hospital dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 35 publications
6
32
2
3
Order By: Relevance
“…Among these, 125 studies were excluded (Figure ). Therefore, six studies that included a total of 741 743 patients were selected for full analysis (Table ). There were two record‐linkage clinical studies, three data‐based studies and one study based upon a nationwide audit .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 125 studies were excluded (Figure ). Therefore, six studies that included a total of 741 743 patients were selected for full analysis (Table ). There were two record‐linkage clinical studies, three data‐based studies and one study based upon a nationwide audit .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, six studies that included a total of 741 743 patients were selected for full analysis (Table ). There were two record‐linkage clinical studies, three data‐based studies and one study based upon a nationwide audit . Four studies reported 3‐month mortality, one study reported 12‐month mortality, and one study reported both 3‐ and 12‐month mortalities of ASUC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are incorporated along with other health and social services data in the Secure Anonymised Information Linkage (SAIL) Databank,33,34 funded by the Welsh Assembly Government since 2006 and stored on an IBM supercomputer in the College of Medicine, Swansea University. These data have been used as the basis of many published studies in international Medline journals 3540. The hospital in-patient data used, the Patient Episode Database for Wales (PEDW), includes abstracts of in-patient and day case admissions to all National Health Service (NHS) hospitals in Wales.…”
Section: Methodsmentioning
confidence: 99%
“…Ulcerative colitis (UC) is one of the major forms of inflammatory bowel disease (IBD), which additionally includes Crohn's disease and indeterminate colitis, all characterized by idiopathic chronic inflammation of the gastrointestinal tract [1].…”
Section: Introductionmentioning
confidence: 99%